Facile synthesis of nanosized graphene/Nafion hybrid materials and their application in electrochemical sensing of nitric oxide - Yusoff, N.; Pandikumar, A.; Marlinda, A.R.; Huang, N.M.; Lim, H.N. (Royal Society of Chemistry, 2015)
This paper presents the preparation of nanosized graphene hybridized with Nafion using a simple two step, sonication and hydrothermal process which successfully produced a new nanosized graphene-Nafion hybrid (G-Nf) with lateral dimensions as small as 18 nm based on AFM results. The novel G-Nf hybrids were used to modify the glassy carbon electrode (GCE) for the fabrication of nitric oxide (NO) electrochemical sensors where the optimum sensing response was achieved with a G-Nf hybrid synthesized after 16 h of hydrothermal treatment. Under the optimized experimental conditions, the GC/G-Nf (16 h) electrode showed an oxidation peak at 0.85 V in the presence of NO. It also demonstrated an excellent performance toward the detection of NO, with a limit of detection of 11.61 μM (S/N = 3) in a linear range of 0.05-0.45 mM. Moreover, this GC/G-Nf (16 h) electrode exhibited a higher sensitivity of approximately 62 μA mM-1 and had a great selectivity toward NO in the presence of interferents such as dopamine and ascorbic acid. The combination of nanosized graphene and Nafion generates a synergic effect which facilitates excellent electron-transfer processes between the electrolyte and the GCE thus improving the sensing performance of the fabricated modified electrode.